Предмет: Математика,
автор: assasin20064
a(a+2)*(a+4)*(a+8), a=3 b(b-2)*(b-6)*(b-8),b=13
Ответы
Автор ответа:
0
Просто подставить нет?
3*(3+2)*(3+4)*(3+8)=3*5*7*12=1260
13*(13-2)*(13-6)*(13-8)=13*11*7*5=5005
3*(3+2)*(3+4)*(3+8)=3*5*7*12=1260
13*(13-2)*(13-6)*(13-8)=13*11*7*5=5005
Автор ответа:
0
:D cпс
Автор ответа:
0
нет
Автор ответа:
0
нужно сократить
Автор ответа:
0
ну так сокращай
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Химия,
автор: gydgwj
Предмет: География,
автор: yanaprotsyshyna1
Предмет: История,
автор: natkaforks
Предмет: Литература,
автор: лилечкаааляля